(untitled) (History Journal «Jerónimo Zurita», 2023)
This research discusses the part played by the Order in the life of the twenty medieval Cistercian nunneries in the Crown of Aragon. The survey of their collections of charters, of the remains of their libraries and of the central documentation of the Order shows that the Cistercian actors, be it the central authorities of the Order or the local abbeys, male or female, played a less important part than historiography has hitherto assumed, particularly in the key moments of their foundation or suppression. In the ordinary course of their existence, their abbot father and, from the middle of the 14th century, the visitor and general reformer of the Order in Aragon played locally an intermittent role, but they had few direct contacts with other female monasteries or with the General Chapter of Cîteaux.